Socioeconomic position during pregnancy and pre-school exposome in children from eight European birth cohort studies - Pizzi, Costanza; Moirano, Giovenale; Moccia, Chiara; Maule, Milena; D'Errico, Antonio; Vrijheid, Martine; Cadman, Timothy J.; Fossati, Serena; Nieuwenhuijsen, Mark; Beneito, Andrea; Calas, Lucinda; Duijts, Liesbeth; et al. (Social science & medicine (1982), 2024)
Distribution of environmental hazards and vulnerability to their effects vary across socioeconomic groups. Our objective was to analyse the relationship between child socioeconomic position (SEP) at birth and the external exposome at pre-school age (0–4 years). This study included more than 60,000 children from eight cohorts in eleven European cities (Oslo, Copenhagen, Bristol, Bradford, Rotterdam, Nancy, Poitiers, Gipuzkoa, Sabadell, Valencia and Turin). SEP was measured through maternal education and a standardised indicator of household income. Three child exposome domains were investigated: behavioral, diet and urban environment. We fitted separate logistic regression model for each exposome variable - dichotomised using the city-specific median - on SEP (medium/low vs high) adjusting for maternal age, country of birth and parity. Analyses were carried out separately in each study-area. Low-SEP children had, consistently across study-areas, lower Odds Ratios (ORs) of breastfeeding, consumption of eggs, fish, fruit, vegetables and higher ORs of TV screen time, pet ownership, exposure to second-hand smoke, consumption of dairy, potatoes, sweet beverages, savory biscuits and crisps, fats and carbohydrates. For example, maternal education-breastfeeding OR (95% Confidence Interval (CI)) ranged from 0.18 (0.14–0.24) in Bristol to 0.73 (0.58–0.90) in Oslo. SEP was also strongly associated with the urban environment with marked between-city heterogeneity. For example, income-PM2.5 OR (95%CI) ranged from 0.69 (0.47–1.02) in Sabadell to 2.44 (2.16–2.72) in Oslo. Already at pre-school age, children with lower SEP have consistently poorer diets and behaviours, which might influence their future health and wellbeing. SEP-urban environment relationships are strongly context-dependent. •Harmonised data on 61378 children from eight cohorts in eleven European cities.•Two indicators of socioeconomic position (SEP): household income and maternal education.•Low SEP children had consistently poor diet and unhealthy behaviours at preschool age.•SEP-urban environment relationships are strongly context-dependent.•The preschool age period is a window of opportunity to mitigate SEP inequalities.